Risk Management, Leverage, Firm Size, and Their Effect on Financial Performance - Vanessa Florencia; Victoria Ari Palma Akadiati; Agnes Susana Merry Purwati (International Forum of Researchers and Lecturers, 2026)
This study aims to examine and analyze the effect of risk management, measured using the Enterprise Risk Management Disclosure Index (ERMDI), leverage, and firm size on corporate financial performance. This research employs a quantitative approach using secondary data obtained from annual reports and financial statements of companies listed on the Indonesia Stock Exchange as the research sample during the observation period of 2020 -2024. The sampling technique used was purposive sampling. Data analysis was conducted using multiple linear regression, preceded by classical assumption tests, and hypothesis testing was carried out using t-tests and F-tests. The results show that, partially, leverage and firm size have a significant effect on financial performance, while risk management measured using the ERMDI does not have a significant effect. Simultaneous testing indicates that risk management, leverage, and firm size collectively have a significant effect on financial performance. These findings suggest that funding structure and company scale are more dominant factors in improving financial performance compared to the level of risk management disclosure. This research contributes to the development of literature on the factors influencing financial performance and can serve as a consideration for corporate management in formulating policies related to capital structure management, business scale expansion, and the more effective implementation of risk management.